Optimizing an Electrochemical Protocol for Quantitative Analysis of Ascorbic Acid in Dietary Supplements. Issue 3 (5th November 2021) - Wilson, Patrick; Sorto, Sabrina; Apawu, Aaron K.
Abstract: Electroanalytical techniques are versatile and dynamic tools used extensively in research and industrial applications; however, they are not adequately covered in the undergraduate chemistry curriculum. Herein, a fast‐scan cyclic voltammetry (FSCV) protocol is presented as a simple but efficient method of analysis that can be incorporated into analytical chemistry labs to demonstrate the utility and versatility of electrochemical techniques. The simplicity of ascorbic acid's electrochemistry makes it an excellent candidate for evaluating an electroanalytical method. In this work, flow cell‐based FSCV was used to measure the ascorbic acid content in a dietary supplement. The protocol involved optimization of the excitation waveform and scan rate, and external standard calibration analysis. The method was evaluated using spike recovery and a standard addition analysis as a secondary method of validation. The external calibration method exhibited excellent accuracy (relative error=−0.6 %, Recovery=100.5 %), suggesting no significant matrix effect, high precision (RSD=±0.4 %) and sensitivity (m=2224.4 nA mm −1 ). These observations were comparable to results from the standard addition method as revealed by the statistical analysis. Overall, this work demonstrates the use of a cutting‐edge electroanalytical technique in quality control. Abstract : A versatile electroanalytical protocol that can be adopted in undergraduate analytical chemistry labs to emphasize important electrochemistry concepts is presented. This protocol demonstrates simplicity and utility of an electroanalytical technique in quality control as well as the use of statistics in chemical analysis.